Els poemes valencians de Josep Vicent Ortí. Estudi i edició - Furió Vayà, Joan M. (Caplletra. Revista Internacional de Filologia, 2001)
In this article we are given an overview of the written production of J. V. Ortí, a member of a family of Valencia public notaries who had connections with the municipal government during the XVII century. This author, in spite of his pro-Bourbon ideology stance, often used Catalan in his writings, all of which have been published for the first time.